SYNTHESIS OF NEW 5-(CHROMENE-3-YL)METHYLENE-2,4-THIAZOLIDINEDIONES - NASTASĂ, Cristina; TIPERCIUC, Brînduşa; VLASE, Laurian; PÎRNĂU, Adrian; ONIGA, Ovidiu (Studia Universitatis Babeș-Bolyai Chemia, 2015)
With the aim of developing new biologically active compounds, a series of new N-substituted 5-(chromene-3-yl)methylene-2,4- thiazolidinediones 3-12 has been synthesized. The first step was the condensation of different chromone-3-carbaldehydes with 2,4-thiazolidinedione, followed by the reaction with various α-bromoalkylarylketones. The structures of all new compounds were confirmed by elemental analysis, mass spectra and 1H NMR studies.